Factors influencing attrition from a one-year postpartum lifestyle intervention for women experiencing diabetes in pregnancy - Masuluke, Irene (My University, 2022)
Gestational diabetes mellitus (GDM) is a glucose tolerance disorder detected during pregnancy and has risks for both the mother and fetus. GDM prevalence in South Africa is estimated to be as high as 26%. Women with GDM are at high risk of developing type 2 diabetes mellitus (T2DM) though this risk can be managed by healthy lifestyle interventions. However, attrition from such intervention programmes is still a challenge. Therefore, this study aimed to assess factors affecting women’s attrition from a one-year randomized controlled lifestyle intervention. This was a cross-sectional descriptive-analytic qualitative study nested within an ongoing pilot trial IINDIAGO (Integrated health system intervention aimed at reducing T2DM risk in women after gestational diabetes) in Soweto. Women were recruited from the intervention arm of IINDIAGO using extreme case sampling to create two groups: Group A - “retained women” who received at least 40% of the intervention sessions; Group B - “disengaged women” who received less than 30% of the intervention sessions. Twenty-eight interviews were conducted using a semi-structured topic guide, with transcripts thematically analysed using inductive and deductive approaches. Facilitating factors for retention were the perceived benefits received i.e., friendliness, kindness, and education, and perceived risk of GDM and T2DM interventions. In comparison, disengaged women reported challenges related to their personal situation (work commitments, schedule conflicts, relocation, illness, childcare, travel costs); communication challenges with the intervention team; and fear/anxiety related to medical procedures to the COVID-19 pandemic as reasons for attrition.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of Witwatersrand, Johannesburg, 2022